Automation of Academic and Research Libraries in Karnataka: a Survey of Mysore City - Chandrashekara, M.; Mulla, K. R.; Selvaraja, A. (Journal of Information and Knowledge, 2012)
In Mysore city there are more than 30 academic and research libraries. The investigators have taken only 23 libraries for the study. Out of 23 libraries 17 libraries have computers. In these 17 libraries only 14 libraries have automated their library operations. In this study the investigators have touched various aspects related to library automation. The libraries that have not automated have given reasons for the delay to start automation work. Many libraries have network connections for sharing the information. The libraries operate with MYLIBNET, DELNET and INFLIBNET networking programmes. In many libraries the professional and semi professional staff are involved in data entry work.